Efisiensi Rem Kendaraan Bermotor Mitsubishi L300 Tanpa Beban Dengan Variasi Persentase Tekanan Angin Ban - Muchlisinalahuddin Muchlis nalahuddin; Sagyta Yeniza Putri; Riza Muharni; Dedi Wadianto; Desmarita Leni (Jurnal Teknik Mesin, 2023)
This study aims to analyze the effect of differences in tire pressure on brake testing at the Unit Pelaksana Teknis Daerah (UPTD) Motor Vehicle Testing, Solok Regency, the implementation of this analysis is to find the efficiency and deviation of the braking force on the tool. Test Brake Tester as well as the condition and calibration of the Brake Tester optimally so that the results of the test equipment are accurate so as to reduce errors in the test results. This research was conducted at the Motor Vehicle Testing Building, Solok Regency, with this research it is expected to be able to find the effect of differences in tire pressure on the efficiency and storage of the braking force. From the analysis that has been carried out, it can be concluded that different tire pressures affect the efficiency and deviation of the braking force on the Brake Tester, so it is necessary to check the tires regularly and once a year calibration of the test equipment must be carried out correctly.